Seizures and Epilepsy following Subarachnoid Hemorrhage: A Review on Incidence, Risk Factors, Outcome and Treatment - Ramos, Miguel Bertelli; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
The mortality rates of subarachnoid hemorrhage (SAH) average 51%, and survivors frequently experience acute and long-term neurological conditions, including seizures and epilepsy. The incidence of post SAH-related seizures and epilepsy, its risk factors, outcomes and management are controversial. The present paper aims to discuss these aspects, to provide the pros and cons of different management options of this condition. A review on PubMed was performed encompassing the incidence of seizures and epilepsy following SAH, the risk factors for its occurrence, its related outcomes, and treatment. The incidence of seizures and epilepsy following SAH varies widely in the literature (from 6 to 26%). Some possible risk factors were identified, such as middle cerebral artery (MCA) aneurysm, Hunt and Hess grade III, aneurysm clipping, thick subarachnoid clot, intracerebral hemorrhage, rebleeding, ischemic brain infarction, Fisher grade III or IV, acute hydrocephalus, hypertension history and poor World Federation of Neurosurgical Societies (WFNS) grade. Nevertheless, these relations are frequently uncertain. Also, it appears that the outcome of patients who suffered SAH is worsened by seizures. Given these uncertainties, the need for antiepileptic drug (AED) prophylaxis, the choice of the best drug and dose, as well as the duration of the treatment are controversial topics. However, some recommendations based on low quality evidence are reasonable to be adopted. These include considering AED prophylaxis when a seizure occur after SAH, considering routine long-term AED prophylaxis in specific populations, considering electroencephalogram (EEG) monitoring, and avoiding phenytoin prescription. That is, an individualized approach appears to be the best option, since there is no high-quality evidence.
Keywords: subarachnoid hemorrhage; epilepsy; incidence; risk factors; anticonvulsants; prognosis